Regulation of DNA Methylation During Plant Endosperm Development - Lu, Dongdong; Zhai, Jixian; Xi, Mengli (Frontiers in Genetics, 2022)
The endosperm is a vital storage tissue in plant seeds. It provides nutrients to the embryos or the seedlings during seed development and germination. Although the genetic information in the endosperm cannot be passed directly to the next generation, its inherited epigenetic marks affect gene expression and its development and, consequently, embryo and seed growth. DNA methylation is a major form of epigenetic modification that can be investigated to understand the epigenome changes during reproductive development. Therefore, it is of great significance to explore the effects of endosperm DNA methylation on crop yield and traits. In this review, we discuss the changes in DNA methylation and the resulting imprinted gene expression levels during plant endosperm development, as well as their effects on seed development.